A Review on Reliability of Integrated Electricity-Gas System - You Zhou; Chuan He (Energies, 2022)
With the development of society and the increase in energy demand, the electric power system and natural gas system become larger and larger, where the network is increasingly complex. The continuous and stable supply of energy is also important. The reliability evaluation of the power system and natural gas system is an essential part of maintaining efficient operation of the system. In this paper, the concept of the integrated electricity-gas system is introduced first, and then the importance of the reliability evaluation of the power system and natural gas system is emphasized. In addition, the main reliability indices and reliability evaluation method of the two systems are presented, and some practical examples are given. Finally, conclusions on the reliability evaluation of the integrated electricity-gas system are drawn.